Aspectos da sistemática não-cumulativa da Cofins - Marquardt, Mário Eduardo (2009)
This work aims at the systematic construction of non-cumulative Cofins from the Federal Constitution. For its production focus, initially, our analysis in the context in which inserted the constitutional principle of non-cumulative, identifying the minimum content of meaning applies to all taxes to which the Magna Carta provides your requirement. Since then, point out the limits that guide the implementation of non-cumulative Cofins by the ordinary legislator and then pass the review of Law 10.833/2003, when it built the rule of law-matrix to credit and the proposed the systematic non-cumulative tax